HOW ORGANIZATIONAL CULTURE AND DIGITAL TRANSFORMATIONAL LEADERSHIP AFFECT EMPLOYEE PERFORMANCE: A STUDY ON JOB SATISFACTION AS A MEDIATOR - Wanda Novita; Sinta Oktavina; Siwi Putri Andini (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The evolving landscape of public sector human resource management demands that health service institutions continuously adapt their leadership approaches and organizational culture to sustain employee productivity. This study investigates the influence of organizational culture and digital transformational leadership on employee performance, with job satisfaction serving as a mediating variable, among employees of a public health service institution in Jakarta, Indonesia. Using a quantitative approach, data were collected from 345 respondents—comprising both permanent and contract employees—through a structured questionnaire employing a 1–5 Likert scale. Data analysis was conducted using Structural Equation Modelling (SEM) assisted by SmartPLS 4.0 software. The findings reveal that organizational culture and digital transformational leadership positively and significantly influence job satisfaction. Furthermore, job satisfaction and digital transformational leadership positively and significantly influence employee performance. However, organizational culture does not exert a direct significant effect on employee performance. Indirect path analysis confirms that job satisfaction fully mediates the relationship between organizational culture and employee performance, and partially mediates the relationship between digital transformational leadership and employee performance. These results underscore the critical role of job satisfaction as a mechanism through which culture and leadership shape performance outcomes in the public health sector